Self Efficacy dan Pengalaman Auditor Terhadap Kualitas Audit yang Dimoderasi oleh Kecerdasan Emosional - Kharisma, Dewi Ayu Nita; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 32 No 2 (2022)DO - 10.24843/EJA.2022.v32.i02.p11, 2022)
This study aims to examine the effect of self-efficacy and auditor experience on audit quality moderated by emotional intelligence. This research was conducted at Public Accounting Firms in the Provinces of Bali and Java using primary data obtained from questionnaires. The population in this study amounted to 269, the method of determining the sample using the purposive sampling method with 117 auditors as respondents, consisting of 63 auditors at the Bali Province Public Accounting Firm, 19 auditors in East Java, 10 auditors in Central Java, and 25 auditors in West Java. The data analysis technique used is the moderated regression analysis (MRA) interaction test of moderating variables. The results of the analysis show that self-efficacy has a positive effect on audit quality, auditor experience has a positive effect on audit quality, emotional intelligence strengthens the effect of self-efficacy on audit quality, emotional intelligence strengthens the effect of auditor experience on audit quality.perience on audit quality. Keywords: Self Efficacy; Auditor Experience; Emotional Intelligence; Audit Quality .